Sleep in the time of COVID-19: findings from 17000 school-aged children and adolescents in the UK during the first national lockdown. Issue 1 (19th January 2022) - Illingworth, Gaby; Mansfield, Karen L; Espie, Colin A; Fazel, Mina; Waite, Felicity
Abstract: Study Objectives: Sleep is essential to young people's wellbeing, yet may be constricted by the adolescent delayed sleep phase coupled with school start times. COVID-19 restrictions caused major disruptions to everyday routines, including partial school closures. We set out to understand changes in students' self-reported sleep quality, and associations with mental wellbeing and interpersonal functioning, during these restrictions. Methods: The OxWell school survey—a cross-sectional online survey—collected data from 18 642 children and adolescents (aged 8–19 years, 60% female, school year 4–13) from 230 schools in southern England, in June–July 2020. Participants completed self-report measures of the impact of COVID-19 restrictions on sleep quality, happiness, and social relationships. Sleep timing was compared with data collected from 4222 young people in 2019. Results: Females and older adolescents were more likely to report deteriorations in sleep during the national lockdown. Regression analysis revealed that changes in happiness (β = .34) and how well students were getting on with others in their household (β = .07) predicted change in sleep quality. Students' bedtimes and wake times were later, and sleep duration was longer in 2020 compared to the 2019 survey. Secondary school students reported the greatest differences, especially later wake times. Conclusions: During COVID-19 restrictions, sleep patterns consistent with adolescent delayed sleep phase were observed, with longer sleep times for secondary school students in particular. Perceived deteriorations in sleep quality were associated with reductions in happiness and interpersonal functioning, highlighting the importance of including sleep measures in adolescent wellbeing research.